2017
DOI: 10.14295/2238-6416.v72i2.580
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade De Bactérias (Starter E Probióticas) Em Bebidas Elaboradas Com Iogurte E Polpa De Manga

Abstract: RESUMOEste trabalho teve como objetivo desenvolver duas formulações de bebida probiótica do tipo smoothie com iogurte e polpa de manga (F1 e F2), bem como avaliar a viabilidade dos microrganismos, a qualidade higiênico sanitária e as características físico-químicas (pH, acidez e sinérese) das bebidas ao longo de 30 dias de estocagem refrigerada. F1 foi preparada com adição de 30% de polpa de manga e 10% de açúcar ao iogurte probiótico e F2 foi adicionada de 40% de polpa e 8% de açúcar. A qualidade higiênico-sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…A significant increase in acidity was observed during storage, especially for the formulation F1 made with COS-Glc, which may have led to a higher syneresis rate of the beverages throughout the storage. Barbosa;Gallina (2017) also observed a significant increase in syneresis during the storage of yogurts, especially at 30 days, with similar values to the formulation F2 (without COS-Glc) containing 40% mango pulp.…”
Section: Physicochemical Characterizationsupporting
confidence: 60%
See 3 more Smart Citations
“…A significant increase in acidity was observed during storage, especially for the formulation F1 made with COS-Glc, which may have led to a higher syneresis rate of the beverages throughout the storage. Barbosa;Gallina (2017) also observed a significant increase in syneresis during the storage of yogurts, especially at 30 days, with similar values to the formulation F2 (without COS-Glc) containing 40% mango pulp.…”
Section: Physicochemical Characterizationsupporting
confidence: 60%
“…No changes in L. bulgaricus counts were observed for the formulation F2. Barbosa;Gallina (2017) found similar viable counts of S. thermophilus and L. delbrueckii subsp. bulgaricus in smoothie beverages made with probiotic yogurt and mango pulp.…”
Section: Viability Of Yogurt and Probiotic Culturesmentioning
confidence: 85%
See 2 more Smart Citations
“…Acidity is an important quality attribute for yoghurts and a factor that limits its acceptance, being a desirable value for yoghurts to have an acidity around of 0.70 -0.72% of lactic acid (Moreira et al, 1999;Tamime et al, 2007). Hossain et al (2012), Gallina et al (2012) and Barbosa et al, (2017) also observed an increase in acidity and a decrease in pH of yogurts containing fruit pulp. The symbiotic beverages presented titratable acidity values similar to those observed for fermented milk, usually between 0.6 and 1.0 g of lactic acid per 100 g of product (Brasil, 2007).…”
Section: Resultsmentioning
confidence: 88%